Pengelolaan Perpustakaan di MA Negeri 1 Kebumen - Ahmad Zaenul Muttaqin; Benny Kurniawan; Maryanto Maryanto (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
The purpose of this study is to find out how the library management in Madrasah Aliyah Negeri 1 Kebumen. The approach used in this research is qualitative with qualitative descriptive research methods. The subjects of this study were 1 head of the library and 1 staff of library technical services. Data collection techniques in this study using interviews, observation, and documentation. The results showed that the management of the Iqra MAN 1 Kebumen Library was carried out by planning a work program covering short, medium and long term work programs. Organizing by library administrators who have been formed and approved by the head of the madrasa. The implementation of the short-term work program has been implemented with a percentage of 100%, the medium-term work program has also been implemented 100%, while the long-term work program has yet to be implemented. Meanwhile, the evaluation of the management of the MAN 1 Kebumen library is carried out every year.